Up-regulation of long non-coding RNA CYTOR induced by icariin promotes the viability and inhibits the apoptosis of chondrocytes - Guoyou Wang; Lei Zhang; Huarui Shen; Qi Hao; Shijie Fu; Xia Liu (BMC, 2021)
Abstract Background Icariin (ICAR) is the main effective component extracted from epimedium, and is reported to have the potential to treat osteoarthritis (OA). However, its pharmacological function on chondrocytes has not been fully clarified. Methods Different doses of ICAR were used to treat chondrocyte cell lines, including CHON-001 and ATDC5. Then the expressions of different lncRNAs were measured by qRT-PCR. Interleukin-1β (IL-1β) was used to simulate the inflammatory response environment of chondrocytes. Overexpression plasmids and short hairpin RNAs of lncRNA CYTOR were used to construct gain-of-function and loss of function models. CCK-8 was conducted to determine the cell viability. Flow cytometry was used to detect the apoptosis of chondrocytes. Enzyme-linked immunosorbent assay (ELISA) was adopted to measure the contents of inflammatory factors (IL-6, IL-8, TNF-α) in the supernatant of the chondrocytes. Results Compared with other lncRNAs, CYTOR was changed most significantly in both CHON-001 and ATDC5 cells after treatment with ICAR. ICAR promotes the viability and inhibits the apoptosis of CHON-001 and ATDC5 cells induced by IL-1β, accompanied with reduced levels of inflammatory factors. Overexpression of CYTOR facilitated the viability of chondrocytes, while repressed their apoptosis and inflammatory response. What's more, knockdown of CYTOR reversed the protective effects of ICAR on chondrocytes. Conclusion CYTOR was a pivotal lncRNA involved in the protective function of ICAR on chondrocytes.